Pengaruh Struktur Modal, Pertumbuhan Laba Dan Konservatisme Akuntansi Terhadap Kualitas Laba - Isra Wati Harahap; 2Khoirunnisa Azzahra (Politeknik Raflesia Press, 2025)
This study aims to determine and test the effect of capital structure, profit growth, accounting conservatism on profit quality. The dependent variable in this study is profit quality, while capital structure, profit growth, accounting conservatism are independent variables. The population in this study is the Consumer Non-Cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. The sample used was a purposive sampling technique by setting certain criteria and obtained 34 companies that met the criteria. The analysis model used in this study is panel data regression analysis. Based on the results of the data analysis that has been carried out, it shows that the capital structure of profit growth has an effect on profit quality. While accounting conservatism has no effect on profit quality.